Eco-Pesantren: Analisis Pemahaman Teologi Lingkungan di Pondok Pesantren Al-Ittifaq - Mochammad Mizwar S (Gunung Djati Conference Series, 2023)
This research has a background related to concerns over the recent environmental crisis which can be overcome by the presence of Eco-Pesantren as a real form of participation of Islamic educational institutions in opposing the environmental crisis on divine awareness. This study aims to describe the understanding of environmental theology at Pondok Pesantren Al-Ittifaq Rancabali, Bandung Regency as an Eco-Pesantren and its application in daily life, especially in agricultural activities in Islamic boarding schools. This research uses qualitative research with a case study approach at Al-Ittifaq Islamic Boarding School with the perspective of environmental theology in Islam and the analysis of Farmer Ecotheology as a concept of agricultural theology. The results and discussion of this study Al-Ittifaq as an Islamic educational institution with abundant natural resources shows that the understanding of the importance of maintaining it is based on monotheism that comes from the Qur'an, hadith, and studies of the books of the salaf scholars. From this study, it can be concluded that the Al-Ittifaq Islamic Boarding School in treating the environment at least understands the principles of environmental theology, such as the foundation of monotheism. At the same time, the aspects of environmental concern at Al-Ittifaq represent quite a form of application of environmental theology.